Human homologue of a gene mutated in the slow Wallerian degeneration (C57BL/Wld(s)) mouse. - Fernando, F; Conforti, L; Tosi, S; Smith, A; Coleman, M (2002)
The slow Wallerian degeneration mouse (C57BL/Wld(s)) is a mutant strain of mouse, with the unique phenotype of prolonged survival of the distal axon following axotomy. The causative mutation is an 85 kb tandem triplication on distal mouse chromosome 4. The dominant slow Wallerian degeneration phenotype is conferred by a hybrid gene within the triplication, comprising a gene of previously unknown function, D4Cole1e, and the 5' end of ubiquitination factor E4B (Ube4b). It encodes an in-frame fusion protein consisting of the N-terminal 70 amino acids of Ube4b and 303 amino acids derived from the D4Cole1e gene. We have identified the human homologue of D4Cole1e, and mapped it to chromosome 1p36.2. Additional fluorescence in situ hybridisation signals indicate the presence of several homologous human sequences. Northern blot analysis shows two transcripts, widely expressed at varying levels in different human tissues. The human cDNA, which encodes a protein of 279 amino acids, has 80% nucleotide identity with the mouse cDNA. The derived human and mouse protein sequences share 78% amino acid identity and 82% amino acid similarity. The human cDNA and protein sequences are identical to the human nicotinamide mononucleotide adenylyltransferase (NMNAT). We have also determined the intron/exon structure of the gene, which will facilitate the screening of these exons for mutations in human neurodegenerative disorders.